Evidence of Antitumor and Antimetastatic Potential of Induced Pluripotent Stem Cell-Based Vaccines in Cancer Immunotherapy - Kishi, Masae; Asgarova, Afag; Desterke, Christophe; Chaker, Diana; Artus, Jérôme; Turhan, Ali G.; Bennaceur-Griscelli, Annelise; Griscelli, Frank (Frontiers in Medicine, 2021)
Cancer is maintained by the activity of a rare population of self-renewing “cancer stem cells” (CSCs), which are resistant to conventional therapies. CSCs over-express several proteins shared with induced pluripotent stem cells (iPSCs). We show here that allogenic or autologous murine iPSCs, combined with a histone deacetylase inhibitor (HDACi), are able to elicit major anti-tumor responses in a highly aggressive triple-negative breast cancer, as a relevant cancer stemness model. This immunotherapy strategy was effective in preventing tumor establishment and efficiently targeted CSCs by inducing extensive modifications of the tumor microenvironment. The anti-tumoral effect was correlated with the generation of CD4+, CD8+ T cells, and CD44+ CD62L- CCR7low CD127low T-effector memory cells, and the reduction of CD4+ CD25+FoxP3+ Tregs, Arg1+ CD11b+ Gr1+, and Arg1+ and CD11b+ Ly6+ myeloid-derived suppressor cell populations within the tumor. The anti-tumoral effect was associated with a reduction in metastatic dissemination and an improvement in the survival rate. These results demonstrate for the first time the clinical relevance of using an off-the-shelf allogeneic iPSC-based vaccine combined with an HDACi as a novel pan-cancer anti-cancer immunotherapy strategy against aggressive tumors harboring stemness features with high metastatic potential.